ESTIMATING THE IMPACT OF THE SECTORAL DISTRIBUTION OF CREDIT GRANTED BY COMMERCIAL BANKS ON THE GROSS DOMESTIC PRODUCT AND THE ADDED VALUE OF AGRICULTURE IN IRAQ - S. A. Hammad (مجلة الأنبار للعلوم الزراعية)
This paper aims to estimate and measure the impact of credit granted to the agricultural sector (loans and advances) from commercial banks on the gross domestic product and value added to Iraq's agriculture for 2008-2022. The autoregressive distributed lag (ARDL) model measured the relationship between variables. The results show a cointegration relationship between the credit granted to loans and advances in GDP and value added to agriculture. The results show a positive long-term relationship between the credit granted to loans and advances and GDP at the level of (10%). A positive long-term relationship exists between the credit granted to loans and advances and the value added to agriculture at 10%. The paper recommends increasing the allocation of loans and advances towards the agricultural sector to increase production and meet the local demand for agricultural products, which will reflect economic growth. There is a need for optimal and efficient exploitation of agricultural loans, monitoring, and auditing to ensure that they are spent for their intended purposes and not leaked to destinations other than agriculture